2019
DOI: 10.1016/s2468-2667(19)30077-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk of childhood psychiatric disorders in children of refugee parents with post-traumatic stress disorder: a nationwide, register-based, cohort study

Abstract: Background Children of refugees are often exposed to the consequences of parental post-traumatic stress disorder (PTSD), potentially leaving them vulnerable to intergenerational transmission of psychopathology. The present study aimed to determine whether parental PTSD is associated with childhood psychiatric morbidity among children of refugees. Methods This study is a two-generation nationwide cohort study using the Danish Immigration Services database. We followed up children younger than 18 years with at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Other research studies indicated that the odds of having difficult children is higher in parents with mental disorders. [ 25 ] Disorganization within the family system reduces the cohesion and efficiency of these families. Disorganized and poly-problematic families fail to meet their children's necessities.…”
Section: Discussionmentioning
confidence: 99%
“…Other research studies indicated that the odds of having difficult children is higher in parents with mental disorders. [ 25 ] Disorganization within the family system reduces the cohesion and efficiency of these families. Disorganized and poly-problematic families fail to meet their children's necessities.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the International Classification of Diseases 11th Revision (ICD-11), complex PTSD is described with similar core symptoms of re-experiencing, avoidance, and a sense of current threat alongside disturbances of self-organization which can include affect dysregulation, negative self-concept, and disturbances in relationships (5). These presenting features, in conjunction with primary caregivers often exposed to the same experiences (6)(7)(8), raise additional complexities in getting children with PTSD to enter and remain in treatment. For example, a core component of the disorder being treated is avoidance of any reminder of the original traumatic event.…”
Section: Introductionmentioning
confidence: 99%
“…Children whose parents have been traumatized by war and torture are thus an especially vulnerable group. Having a parent with PTSD increases the risk of behavioural issues and mental health problems, among the offspring (19–23). Especially maternal PTSD and depression have been linked to child distress (19, 20, 24, 25).…”
Section: Introductionmentioning
confidence: 99%
“…Especially maternal PTSD and depression have been linked to child distress (19, 20, 24, 25). Yet significant correlations have been found between both maternal and paternal PTSD diagnosis and the child's risk of developing mental health problems (22, 23). Moreover, parental traumatic experiences in refugee families have been identified as a risk factor for violence (26), and a systematic review found that child abuse was consistently more prevalent in trauma‐exposed populations (27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation